Experimental and numerical analysis of low-velocity impact damage of CFRP laminates with rubber protective layer. (15th November 2022) - Li, Ximing; Liang, Biao; Liu, Ping; Cheng, Hui; Cao, Sipeng; Zhang, Kaifu
Abstract: Carbon fiber reinforced polymers (CFRP) are widely used nowadays as primary and secondary bearing structures in the aviation industry. However, CFRP structures are threatened by unpredictable low-velocity impact events (caused by dropped tools, etc.) during the assembly process, which can cause impact damages. To prevent CFRP damage during the assembly process, a rubber layer can be placed on the surface of the CFRP to form a protective hybrid structure. The influence of rubber layer thickness on the protection effect and on the impact response of the hybrid structure were first investigated in this study. The experimental results indicate that the rubber layer significantly improved the CFRP's impact resistance, with fewer damage modes and less damage area observed. Furthermore, the thicker the rubber layer places, the lower the CFRP delamination position occurs. The whole impact process of this hybrid structure was simulated using the mixed-mode damage criterion for CFRP laminate and the hyperelastic law for the rubber layer. The finite element model was refined with mesh size and contact behavior corresponding to the experiment condition, which showed good agreements with impact response and delamination area experiments. Some internal damage details and damage evolution were also discussed using the finite element model.